COMMUNITY ANIMAL HEALTH SERVICE (YANDUWAN) TO IMPROVE LIVESTOCK HEALTH STATUS FOR TRADITIONAL FARMERS IN KONTENG SUB-VILLAGE, SLEMAN - Winarsih, Sugi; Nugraheni, Yudhi Ratna; Awaludin, Aan (Jurusan Peternakan Politeknik Pertanian Negeri Kupang, 2023)
Livestock from the ruminant group is the commodity most commonly kept by traditional farmers. The availability of animal health services for traditional farmers is important to improve the quality of livestock health. Community Animal Health Services (YANDUWAN) is actively conducted by visiting livestock groups or villages and providing livestock health services needed by traditional farmers. The partners in this activity are traditional farmers in the Konteng sub-village, Sumberadi village, Mlati district, Sleman regency, D.I. Yogyakarta. The methods used were counseling, FMD (Foot and Mouth Disease) vaccination services, vitamin administration, and deworming. YANDUWAN aims to improve traditional farmers' thoughtful of livestock health and improve the quality of livestock health and welfare in traditional farmers. The results achieved, traditional farmers were active in discussing livestock health, especially discussions about FMD, FMD vaccination for 13 cattles (1st vaccination) and 16 cattles (3rd vaccination), FMD vaccination marking for 13 cattles, vitamin administration for 35 cattles, and deworming for 8 cattles. The conclusion that can be presented is that traditional farmers understand more about the importance of livestock health and increase vigilance for disease prevention in ruminants by being willing to carry out recommended vaccinations on their livestock and other treatments for disease prevention.